197k views
4 votes
Using radicals, write an equivalent expression for the expression 2^1/3

User Bwizzy
by
5.8k points

2 Answers

6 votes
2^(1/3)
∛2

The cubed root of two.
User Arosha
by
6.2k points
2 votes

Answer:


2^(1)/(3) =\sqrt[3]{2^1}=\sqrt[3]{2}

Explanation:

2^1/3

We need to write the given expression in radical form

to convert expression into radical form we use formula


a^(m)/(n) =\sqrt[n]{a^m}

The denominator n in the fraction comes with the radical

numerator 'm' goes inside the radical


2^(1)/(3) =\sqrt[3]{2^1}=\sqrt[3]{2}

User Guillermo Barreiro
by
5.6k points